Sposoby tworzenia czasownikowych gniazd słowotwórczych przez dzieci w wieku przedszkolnym - Ejsmunt-Wieczorek, Izabela (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The key objective of this article is to supplement few existing works concerning linguistic skills of pre-school children in relation to word building. The article discusses the topics of children’s verbal word-formation development in the speech ontogenesis. To describe this phenomenon, a nest analysis is used, which, in a clear manner allows to capture derivative techniques and word-formation means used on different levels of linguistic system by 5 year-olds. The nest description method, although wide-spread in linguistics, has not been used in speech therapy research, so far. The article is the first one which presents, how a pre-school child supplements subsequent levels of a given word-formation nest in relation to a verbal derivation.